Cholinergic Abnormalities, Endosomal Alterations and Up-Regulation of Nerve Growth Factor Signaling in Niemann-Pick Type C Disease - Cabeza Carolina; Figueroa Alicia; Lazo Oscar M; Galleguillos Carolina; Pissani Claudia; Klein Andrés; Gonzalez-Billault Christian; Inestrosa Nibaldo C; Alvarez Alejandra R; Zanlungo Silvana; Bronfman Francisca C (Molecular Neurodegeneration, 2012)
Abstract Background Neurotrophins and their receptors regulate several aspects of the developing and mature nervous system, including neuronal morphology and survival. Neurotrophin receptors are active in signaling endosomes, which are organelles that propagate neurotrophin signaling along neuronal processes. Defects in the Npc1 gene are associated with the accumulation of cholesterol and lipids in late endosomes and lysosomes, leading to neurodegeneration and Niemann-Pick type C (NPC) disease. The aim of this work was to assess whether the endosomal and lysosomal alterations observed in NPC disease disrupt neurotrophin signaling. As models, we used i) NPC1-deficient mice to evaluate the central cholinergic septo-hippocampal pathway and its response to nerve growth factor (NGF) after axotomy and ii) PC12 cells treated with U18666A, a pharmacological cellular model of NPC, stimulated with NGF. Results NPC1-deficient cholinergic cells respond to NGF after axotomy and exhibit increased levels of choline acetyl transferase (ChAT), whose gene is under the control of NGF signaling, compared to wild type cholinergic neurons. This finding was correlated with increased ChAT and phosphorylated Akt in basal forebrain homogenates. In addition, we found that cholinergic neurons from NPC1-deficient mice had disrupted neuronal morphology, suggesting early signs of neurodegeneration. Consistently, PC12 cells treated with U18666A presented a clear NPC cellular phenotype with a prominent endocytic dysfunction that includes an increased size of TrkA-containing endosomes and reduced recycling of the receptor. This result correlates with increased sensitivity to NGF, and, in particular, with up-regulation of the Akt and PLC-γ signaling pathways, increased neurite extension, increased phosphorylation of tau protein and cell death when PC12 cells are differentiated and treated with U18666A. Conclusions Our results suggest that the NPC cellular phenotype causes neuronal dysfunction through the abnormal up-regulation of survival pathways, which causes the perturbation of signaling cascades and anomalous phosphorylation of the cytoskeleton.